SIFAT KAYU JATI UNGGUL NUSANTARA (Tectona grandis L.f.) PADA TIGA KELAS DIAMETER POHON - Gudiwidayanto Sapto Putro; Sri Nugroho Marsoem; Joko Sulistyo; Suryo Hadiwinoto (Jurnal Pemuliaan Tanaman Hutan, 2020)
Increasing the growth rate of teak trees is carried out to shorten the tree harvest rotation and reduce the deficit of teak timber supply, while maintaining the superiority of wood properties. The study was conducted to study the nature of five-year-old JUN Teak wood in three classes of tree diameter and radial position of the trunk. This study employed a completely randomized design arranged in factorial combinations of the treatments of radial positions and diameter classes consisting of large (18-22 cm), medium (14-18 cm) and small (10-14 cm) stem diameters, and the radial position of wood on the trunk based on the tree's ring. Three samples of trees were felled for each stem diameter class so that totally nine trees were used in this study. The testing of the physical properties of wood and the measurement of fiber dimensions were conducted using British Standards 373 and the IAWA method, respectively. The results showed that the diameter of the tree and the radial position of the wood had a significant effect on all parameters observed (fiber dimension and physical properties of wood), except the fiber diameter. The tree growth rate had a negative correlation with fiber length (-0.67), fiber wall thickness (-0.65), air-dry moisture content (-0.91) and air dry specific gravity (-0.86), and had a positive correlation with fiber diameter (0.61) and green water content (0.78). According to the pattern of wood properties in the radial direction, JUN wood harvested at the age of five was categorized as juvenile wood. This wood is acceptable as furniture and lightweight construction material.